Coöperatie in spelshows - van den Assem, Martijn J.; van Dolder, Dennie (Amsterdam University Press, 2012)
In this chapter, we argue that game shows can be a useful source of data to study cooperative behavior. The unique combination of well-defined decision problems and large stakes makes game show data complementary to both experimental and field data. Over the past years, a number of TV shows have employed a vari- ant of the prisoner’s dilemma. We summarize the results of five different studies that use these shows to test a broad range of hypotheses. Finally, we discuss caveats of game show data, and contend that the potential problems are mostly not very different from those with experimental and field data.